Martin Buber : the life of dialogue - Friedman, Maurice S. (London ; New York : Routledge, 2002)
Martin Buber: The Life of Dialogue, the first study in any language to provide a complete overview of Buber's thought, remains the definitive guide to the full range of his work and the starting point for all modern Buber scholarship. Maurice S. Friedman reveals the implications of Buber's thought for theory of knowledge, education, philosophy, myth, history and Judaic and Christian belief. This fully revised and expanded fourth edition includes a new preface by the author, an expanded bibliography incorporating new Buber scholarship, and two new appendices in the form of essays on.
pt. 1. Introduction -- pt. 2. Buber's early thought -- pt. 3. Dialogue -- pt. 4. The nature and redemption of evil -- pt. 5. Between man and man -- pt. 6. Between man and God.
Includes bibliographical references (pages 367-392) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Buber, Martin, -- 1878-1965.; Buber, Martin, -- 1878-1965; RELIGION -- Judaism -- Theology